Realität als vermeintliche Grenze der Erkenntnis: Hegels Metaphysik im Anschluss an und in Abgrenzung zu Kant - Plevrakis, Ermylos (Zeitschrift für philosophische Forschung, 2020)
While Kant in his Critique of Pure Reason aims to 'humiliate' reason by declining any possibility of knowledge of things 'in themselves', he does conceive such critique as 'the necessary preparation for a thoroughly scientific system of metaphysics'. In this paper I examine in - what sense Hegel's Science of Logic goes beyond that Kantian view without neither relapsing back into dogmatic metaphysics nor turning into a mere pragmatism. I argue that reality in itself is ontologically deficient so that it is already reality itself (and not just the categories - of understanding) that makes true knowledge of real things impossible. Nonetheless I contend that there is something in Hegel's Science of Logic that is truly absolute and turns Logic into 'a thoroughly scientific system of metaphysics', namely what Hegel calls the Concept or - the Absolute Idea. Furthermore I point out the concrete importance of these metaphysical claims for human theoretical and practical knowledge. This finally provides a new reading of Hegel's Logic as a de-ontologised Aristotelian metaphysics that not just claims to regulate empirical - knowledge in a Kantian manner, but to also conceptually constitute reality 'in itself'.
Gesehen am 01.12.2020